The political economy of Africa's emergent middle class: Retrospect and prospects - Resnick, Danielle (Wiley, 2015)
This special issue introduction provides a historical perspective in order to contextualize the political economy of Africa's emergent middle class. In doing so, three overarching research questions are discussed to better understand the middle class' transformative potential. First, who constitute Africa's middle class and how has this concept changed over time? Second, what dynamics explain the growth of this group? Third, what are the implications of the middle class for good governance and pro‐poor policies? The contributions of each of the articles in the special issue to answering these specific questions for Africa's contemporary middle class are then briefly discussed. © 2015 The Authors. Journal of International Development published by John Wiley & Sons, Ltd.